KEKUATAN PERDAMAIAN YANG DILAKSANAKAN DIDALAM SIDANG PERDATA DI PENGADILAN NEGERI SAMARINDA BERDASARKAN PERMA NO. 01 TAHUN 2016 TENTANG MEDIASI DAN AKIBAT HUKUMNNYA - Majid, Mega Awalia (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACT As individuals who have free will, humans have their own interests. These interests are often in the same direction and in line with the interests of others around them. However, their interests often conflict with each other, giving rise to disputes or disputes that interfere with the harmony of living together. Based on that event, rules are needed as a means to solve problems that arise in order to create balance in life in order to create peace.law enforcers in mediation procedures are mediators and one of the common mediators is judges in district courts. In his duties, a mediator must work according to existing procedures. Due to a change in the mediation procedure through a Supreme Court regulation issued by the government, as for the formulation and limitation of the problem, how is the power of peace implemented in the Samarinda District Court session in relation to Perma no. 1 of 2016 and how is the existence of mediation in the settlement of peace in the Samarinda District Court according to Regulation No. 1 of 2016.The peace deed as outlined in the court's decision has three powers like an ordinary decision, namely binding power, evidentiary power, and executive power. The existence of mediation in the settlement of civil disputes in court in PERMA No. 1 of 2016 contains ten regulatory principles regarding the use of integrated mediation in court (court-connected mediation) which includes mandatory mediation, the autonomy of the parties, mediation in good faith.the disputing parties should be able to carry out problem-solving by means of deliberation before going through a court process which can take time and a lengthy trial process. Keywords: the power of peace, mediation